AUDIT OF THE APPROPRIATENESS OF HEPATOMA SURVEILLANCE IN A COHORT OF PATIENTS ATTENDING A DEDICATED HAEMOCHROMATOSIS CLINIC. (8th June 2013) - Alakkari, A; Gammell, Y; O'Connor, H; McNamara, D; Breslin, N; Ryan, B
Abstract : Introduction: Hereditary Haemochromatosis (HH) remains the commonest genetic disorder in populations of northern European origin with a prevalence of 1 per 220–250. 1 The HH service in Tallaght hospital is an expanding nurse delivered service. Aims/Background: This audit reviews the service in terms of patient demographics, investigations and hepatocellular carcinoma (HCC) surveillance. Method: Data was collected on patients attending the HH service in 2011 who underwent genetic testing. Results: A total of 140 patients were identified; 107 (76%) were male and 33 (24%) female. Median age at diagnosis was 48 and 56 years, respectively. Their genetics were; 101 (74%) C282Y homozygote, 6 (4%) H63D homozygote, 20 (14%) compound heterozygote, 5 (3%) C282Y heterozygote, 2 (1%) H63D heterozygote and 6 (4%) had normal genetics. Mean ferritin and transferrin saturations at diagnosis were 980 µg/l and 75%, respectively. Liver function tests (LFTs) were abnormal at diagnosis in 93(66%) patients. Liver biopsy was performed on 45 patients according to established selection criteria for biopsy. Histology revealed mild fibrosis in 5 patients, bridging fibrosis in 4 and cirrhosis in 4. Patients received monitored weekly venesections as tolerated to achieve a target ferritin<50 µg/l, followed by 3 monthly ferritin monitoring longterm. Patients with cirrhosis and advanced fibrosis were not receiving the recommended HCC surveillance as per AASLD guidelines. 2 3 Conclusion: Appropriate HH management including HHC surveillance for cirrhotic patients and those with advanced fibrosis in accordance with AASLD guidelines requires close patient monitoring and long term follow up. A specialist dedicated nurse delivered service helps to provide this.